SOSIALISASI DAN PELATIHAN (WORKSHOP) PEMANFAATAN LIMBAH ATAU SAMPAH DAUR ULANG SEBAGAI DEKORASI RUANG DALAM (INTERIOR) RUMAH TINGGAL DI KELURAHAN KEBON PALA KOTA ADMINISTRASI JAKARTA TIMUR TAHUN 2021 - Ulinata Ulinata (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Community Service Activities carried out by the Architecture Study Program, Faculty of Engineering UKI with the theme Green Action 25 with the title Socialization and Training (Workshop) on the Utilization of Waste or Recycled Garbage as Interior Decoration for Residential Houses in Kebon Pala Village, East Jakarta Administration City in 2021 This activity is a continuation of the previous Community Service Activity which aims to educate the public about any waste or recycled waste that can be used as a decoration for the interior of a residential house. The method is to hold socialization and training (Workshop) and invite resource persons who are experts in the use of waste or recycled waste so that participants receive education about how to use waste or recycled waste so that it can become a residential interior decoration product. then participants can do it independently at their home and pass it on to their neighbors, relatives and families who have never participated in the socialization and training (workshop). The process is that participants practice directly by making wall hangings from plywood and coffee wrappers, detergents and others using patterns that have aesthetic value. During this workshop, a question and answer session was also held for the participants. The results show that each RW representative in Kebon Pala Sub-district participated in a complete Workshop (Workshop) so that the material presented could be understood and successfully completed wall decorations from detergents and coffee wrappers or other trash properly and had aesthetic value.